MENINGKATKAN KESEJAHTERAAN MASYARAKAT MELALUI PENGOLAHAN KERIPIK SINGKONG (GOWI FARASI) DI DESA BAWONIFAOSO - Waruwu, Opirman (Haga : Jurnal Pengabdian Kepada Masyarakat, 2023)
The community service activity "Processing Cassava Chips (Gowi Farasi) in Bawonifaoso Village" aims to enhance the welfare of the community by utilizing local potential, specifically cassava. This village has abundant cassava resources, yet the community faces challenges in increasing value-added processing. The program includes training on cassava chip processing skills, marketing strategies, and product branding development. The implementation methods consist of socialization, practical training, mentoring, and evaluation to ensure the program’s success. The results show an increase in community skills, the establishment of new businesses, and an increase in income through the marketing of cassava chips. Additionally, positive social impacts are reflected in women’s empowerment and improved family quality of life. This activity has successfully created awareness of the importance of innovation in local product processing. To ensure the sustainability of the business, it is recommended to conduct further training and develop a broader marketing network. This program can serve as a model for the sustainable development of local products and provide long-term benefits for the community